SOME ASPECTS OF AGRICULTURAL DEVELOPMENT FUND FOR THE CITY OF NIS IN 2011 - Zoran Simonović; Dragoljub Simonović; Slavomir Miletić (Ekonomika Poljoprivrede (1979), 2011)
Under modern conditions in which we live emerges is an increasing need to address the problem of rural development. The last reform of the Common Agricultural Policy of the European Union is increasingly devoted attention to the issue of agricultural environment and its planning perspective. This approach stems from new features rural areas. Rural cannot be identifed because the agrarian diversifcation takes place in rural areas.